Pelatihan Manajemen Waktu Pada Organisasi Futsal Di SMA X - Ratnawati, Sri; Fera, Amanda Putri; Pakpahan, Tabita Gabriella; Arifin, Saptyani; Aziz, Abdul (Universitas Negeri Gorontalo, 2024)
This community service activity aimed to improve time management skills among members of a futsal student organization at SMA X, considering the high academic demands that often interfere with organizational participation. The program involved 20 students and employed a quasi-experimental pretest–posttest design, evaluated using Kirkpatrick’s training evaluation model focusing on reaction and learning levels. Reaction level was measured using a Likert-scale questionnaire, while learning level was assessed through time management knowledge tests. The results showed an increase in the mean reaction score from 3.12 (pre-test) to 4.21 (post-test), with a significant difference based on paired samples t-test (p 0.05). At the learning level, the mean score increased from 3.10 to 9.85, with Wilcoxon Signed Rank Test indicating a significant improvement (p 0.05). These findings indicate that time management training effectively enhanced participants’ responses and knowledge, highlighting its importance in supporting student organizations’ effectiveness and sustainability.